Management - Campling, John (John Wiley & Sons Australia, 2008)
Reflecting the growing international importance of the Asian region to the multicultural societies of Australia and New Zealand, the third edition of this best-selling Australasian introductory management text includes a significant increase in the number of Asian case examples used to illustrate key concepts. With its clear insight into the dynamics of management in the workplace of today and the future, 'Management: 3rd Asia-Pacific Edition' provides a sound basis for contemporary management study.